Body talk : 37 voices explore our radical anatomy - Jensen, Kelly (Algonquin Young Readers, an imprint of Algonquin Books of Chapel Hill, 2020)
"Thirty-seven contributors--including model Tyra Banks, gymnast Aly Raisman, and bestselling YA authors--explore the world in their unique bodies through essays, lists, comics, and art, from the award-winning editor of (Don't) Call Me Crazy"--